Legal Analysis of the Rights and Obligations of Financial Institutions Regarding the Loss of Customers' Property Rights Certificates as a Result of Natural Disasters - Eliezer, Ribka; Wartoyo, Franciscus Xaverius (Faculty of Law, Universitas Pekalongan, 2023)
The loss of a customer's Certificate of Ownership (SHM) while it is in the possession of a financial institution as collateral for a loan is a legal issue that has implications for the rights, obligations, and civil liability of the financial institution. This study aims to analyze the legal regulations related to the obligations of financial institutions in storing and securing SHM based on the Banking Law, the Mortgage Law, and civil law provisions governing the relationship between creditors and debtors. In addition, this study examines the legal responsibility of financial institutions if the SHM is lost due to a natural disaster that meets the criteria of force majeure based on Articles 1244 and 1245 of the Civil Code. The method used is normative legal research with a regulatory, legal concept, and doctrinal analysis approach. The results of the study show that financial institutions are required to apply the principle of prudence in the storage of collateral documents, and if the loss occurs due to a natural disaster that is proven to be force majeure, financial institutions can be exempted from liability for compensation. However, financial institutions remain obliged to carry out administrative recovery, including assisting in the process of issuing replacement certificates and ensuring that customers' legal protection remains guaranteed. This study emphasizes the need for stricter document security standards to prevent the risk of loss due to disasters in the future.